The School of Attention and Action: The Relation Between the World of the Child and the Natural Environment in Children’s Magazines Published in the Second Polish Republic on the Example of Płomyk and Płomyczek - Gromadzka, Beata Maria (Porównania, 2022)
The magazines published by Nasza Księgarnia, Płomyk and Płomyczek, were of great importance for the dissemination of the idea of environmental protection during the interwar period. Nature was an important topic of literary works, popular science articles, poems, advice columns, and readers’ letters. The subsequent issues corresponded to the rhythm of the school year and nature’s calendar. The idea of ecological education of Płomyka and Płomyczka was implemented through the concept of coexistence of children, plants, animals in a homogeneous environment. Reflecting on the presence of both plant and animal worlds in the city space and in the rural landscape sensitized the readers to the values and taught them to observe non-human inhabitants of courtyards, parks, gardens, forests and fields. There is a noticeable effort to create a space for communication and understanding of the natural world. The presentation of the concept of ecological education is a reconstruction of the ethical model where children, animals and plants become equal moral subjects, and where relational practices towards the environment and a sense of doing in the surrounding world are shaped.